Pooled patient-level meta-analysis of children and adults completing a computer-based anxiety intervention targeting attentional bias. (December 2016) - Price, Rebecca B.; Wallace, Meredith; Kuckertz, Jennie M.; Amir, Nader; Graur, Simona; Cummings, Logan; Popa, Paul; Carlbring, Per; Bar-Haim, Yair
Abstract: Computer-based approaches, such as Attention Bias Modification (ABM), could help improve access to care for anxiety. Study-level meta-analyses of ABM have produced conflicting findings and leave critical questions unresolved regarding ABM's mechanisms of action and clinical potential. We pooled patient-level datasets from randomized controlled trials of children and adults with high-anxiety. Attentional bias (AB) towards threat, the target mechanism of ABM, was tested as an outcome and a mechanistic mediator and moderator of anxiety reduction. Diagnostic remission and Liebowitz Social Anxiety Scale (LSAS) were clinical outcomes available in enough studies to enable pooling. Per-patient data were obtained on at least one outcome from 13/16 eligible studies [86% of eligible participants; n = 778]. Significant main effects of ABM on diagnostic remission (ABM—22.6%, control—10.8%; OR = 2.57; p  = 0.006) and AB (β* (95%CI) = − 0.63 (− 0.83, − 0.42); p  < 0.00005) were observed. There was no main effect of ABM on LSAS. However, moderator analyses suggested ABM was effective for patients who were younger (≤ 37 y), trained in the lab, and/or assessed by clinicians. Under the same conditions where ABM was effective, mechanistic links between AB and anxiety reduction were supported. Under these specific circumstances, ABM reduces anxiety and acts through its target mechanism, supporting ABM's theoretical basis while simultaneously suggesting clinical indications and refinements to improve its currently limited clinical potential. Highlights: Transdiagnostic remission was 2.5 times higher for active modification vs. control. Anxiety decreased only when training sessions were completed in the laboratory. Social anxiety decreased significantly only in participants < 37 years old. Reductions in anxiety were mediated by reductions in the intervention mechanism, attention bias.